Financial Inclusion and Innovation in Africa: An Overview. (24th December 2014) - Beck, Thorsten; Senbet, Lemma; Simbanegavi, Witness
Abstract : Financial inclusion is gaining attention in African policy circles in view of the recent African growth renaissance, but which has been characterised as non-inclusive. While not conclusively documented in the literature, financial inclusion is viewed among the drivers of inclusive growth. This special issue takes a stock of the extent of, and the factors affecting financial inclusion; the role of cross-border banking in financial deepening and access across Africa and the impacts of financial innovation on access as well as monetary policy. While Africa's banking systems are still shallow relative to peers, substantial progress has been made over the past two decades both in terms of financial inclusion and financial innovation, as well as cross-border banking. While access to finance has improved, the evidence based on the Global Findex database points to substantial heterogeneity within sub-regions of Africa and demographic characteristics. The evidence also suggests that foreign banks from emerging markets, including Africa, have contributed to financial access, but the opposite is the case for foreign banks from Europe and USA. However, challenges remain, including the gap between financial deepening and financial inclusion.